2019
DOI: 10.1021/acs.chemmater.9b00544
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Polymer Hydrogel Photocatalysts with Expandable Photoactive Sites in Water

Abstract: Water compatibility of heterogeneous photocatalytic materials is recently realized by utilizing hydrogels as a support; however, the embedment of photocatalysts in the hydrogels may hinder the photocatalytic activity and the regeneration of materials. Therefore, combining hydrophilicity and high accessibility to the active sites of heterogeneous photocatalysts is highly challenging. Herein, we report the design of a conjugated polymer hydrogel photocatalyst via complexation between a photoactive conjugated pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 61 publications
0
50
0
Order By: Relevance
“…Catalytic supramolecular hydrogels provide a promising solution to this challenge. [15][16][17][18][19] Hydrogel networks can address the solubility problem because hydrophobic aromatic compounds oen associate into the nanober network in water and become reactively accessible. 20 For example, the Meijer 21 and Escuder 22 groups have shown that a self-assembled, 1D ber network enhances catalytic activity compared to its non-assembled counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic supramolecular hydrogels provide a promising solution to this challenge. [15][16][17][18][19] Hydrogel networks can address the solubility problem because hydrophobic aromatic compounds oen associate into the nanober network in water and become reactively accessible. 20 For example, the Meijer 21 and Escuder 22 groups have shown that a self-assembled, 1D ber network enhances catalytic activity compared to its non-assembled counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…[ 21 ] Due to the volume expansion of the conjugated polymers (hydrogel), more active photocatalytic sites are in contact with the pollutants. [ 22 ] Moreover, the hydrogel photocatalysts offer the advantage of easy regeneration and reusability with good stability. [ 22a ] Therefore, the synergistic effect of the simultaneous adsorption and photocatalytic activity of the chitosan and C 3 N 4 , respectively, led to the highest degradation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The cross-linked PÀ FLÀ BT3 could serve as an efficient, recyclable and cost-effective photocatalyst to degrade organic dyes and reduce heavy-metal ions such as Cr VI to Cr III in water. Byun et al [28] synthesized a hydrogel PÀ BTÀ GX by ionic complexation with cross-linked PÀ BTÀ Vim as polycation and poly (arylic acid) as polyanion. PÀ BTÀ GX exhibited excellent water compatibility and could swell well in water, thereby largely expanding the active sites for photocatalytic reactions.…”
Section: Conjugated Polyelectrolytes/molecular Electrolytesmentioning
confidence: 99%
“…The cross‐linked P−FL−BT3 could serve as an efficient, recyclable and cost‐effective photocatalyst to degrade organic dyes and reduce heavy‐metal ions such as Cr VI to Cr III in water. Byun et al . synthesized a hydrogel P−BT−GX by ionic complexation with cross‐linked P−BT−Vim as polycation and poly (arylic acid) as polyanion.…”
Section: Hydrophilic Conjugated Materials For Photocatalytic Applicatmentioning
confidence: 99%